2014
DOI: 10.1186/1471-2407-14-164
|View full text |Cite
|
Sign up to set email alerts
|

Cyr61 Expression is associated with prognosis in patients with colorectal cancer

Abstract: BackgroundCysteine-rich 61 (Cyr61), a member of the CCN protein family, possesses diverse functionality in cellular processes such as adhesion, migration, proliferation, and survival. Cyr61 can also function as an oncogene or a tumour suppressor, depending on the origin of the cancer. Only a few studies have reported Cyr61 expression in colorectal cancer. In this study, we assessed the Cyr61 expression in 251 colorectal cancers with clinical follow up.MethodsWe examined Cyr61 expression in 6 colorectal cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 34 publications
(48 reference statements)
0
29
0
Order By: Relevance
“…CYR61 has been previously linked to tumor progression in PDAC, as well as several other tumor types including breast, gastric and colorectal cancers [49], [50], [51], [52], [53]. Moreover, prior work suggested that CYR61 expression is regulated by WNT/β-catenin signaling in hepatocellular carcinoma cells [54].…”
Section: Resultsmentioning
confidence: 99%
“…CYR61 has been previously linked to tumor progression in PDAC, as well as several other tumor types including breast, gastric and colorectal cancers [49], [50], [51], [52], [53]. Moreover, prior work suggested that CYR61 expression is regulated by WNT/β-catenin signaling in hepatocellular carcinoma cells [54].…”
Section: Resultsmentioning
confidence: 99%
“…Cyr61 is a multifunctional protein involved in human CRC development and progression [23]. Overexpression of Cyr61 may induce the EMT, thereby leading to cancer cell invasion, metastasis, and poor prognosis [24,27].…”
Section: Discussionmentioning
confidence: 99%
“…Cyr61 is up regulated in many cancers, such as breast [19], esophagus [22], and colorectal cancers [23]. Several studies have reported that Cyr61 promotes the EMT and tumor metastasis [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Since CCN1 can be detected in cerebrospinal fluid it might serve as prognostic marker. Jeong et al (2014) examined CCN1 expression in six colorectal cell lines and 20 sets of paired normal and tumor tissues by western blot. 4/6 lines were higher in CCN1 and 16/ 20 tumor tissues.…”
Section: Ccn Proteins and Cancermentioning
confidence: 99%